Application of Gamma Algorithm in Ink Drop Forming Process - Zhang, Yang; Lu, Likun; Zeng, Qingtao (2020 IEEE 6th International Conference on Computer and Communications (ICCC), 2020)
Droplet forming plays an important role in inkjet control system, especially in substrate imaging. To this end, we used the principle of Gamma algorithm to correct the ink droplet image taken by CCD camera to analyze the forming state of the ink droplet and analyze the shape change of the formation and spreading process of the ink droplet under the fluid with different viscosity and surface tension. By analyzing the contrast of the image formed by the droplet in different Gamma values, the droplet forming state was simulated and analyzed by MATLAB/Simulink simulation tool. The analysis results show that the analysis of the droplet image at Gamma=0.5 can get the best effect. Through the analysis of the droplet image, we detected that the droplet formed the best state when the viscosity was 10Pa·s and the surface tension was 40mN/m. In this way, we could also print the best picture on the substrate. Finally, we were able to design the best ink-jet printing system.